Impact of the Layering of Blast-Induced Damage Factors in the Hoek–Brown Failure Criterion on the Bench Damage Monitoring of Mines (Rudarsko-geološko-naftni zbornik, 2023)
The process of creating a slope in a rock mass using the excavation and blasting methods consistently leads to stress release in the rock mass, resulting in a certain level of fracture and disturbance. Blast-induced vibrations can also influence the quality of the rock mass remaining after the blasting, as well as the stability and bench damage monitoring (BDM) of mines. A damage factor (D) is included in the Hoek–Brown failure criterion to compute the disturbance of a rock mass in creating a slope. Choosing the value and thickness of the blast zone for the Hoek–Brown criterion is crucial in the safety analysis and BDM of mines. However, the selection is still a crucial technical challenge in this criterion. Employing nonlinear layering, the present study divides the rock mass behind a blast hole into several layers with decreasing D values applied to each layer. The numerical simulation was conducted using the FLAC finite difference software for bench vibration assessment and damage monitoring by checking the peak particle velocity (PPV) in the bench face with different geometries. Behind the blast hole, five different layers of D were considered through which the Hoek–Brown properties of the rock mass declined nonlinearly during the execution of the model. Since the disturbance threshold of PPV was assumed to be 120 mm/s, the toe and middle parts of the small benches were in the disturbance threshold, while for the medium and high benches, only the bench toe was within the disturbance threshold.